Reimagining Bullion Markets: Blockchain as an Anti-Fraud Mechanism and Digital Transparency - Muhammad Hikmal Yazid (Journal of Economic, Business & Accounting Research, 2026)
Background: The digitalization of bullion trading has transformed the way precious metals are traded and accessed by investors. Alongside these developments, concerns regarding transparency, asset verification, and fraud prevention have become increasingly important. This study aims to examine the potential role of blockchain technology in enhancing transparency and supporting anti-fraud mechanisms within digital bullion markets. Methods: This study employs a conceptual literature review approach by synthesizing recent studies on blockchain, digital finance, market transparency, and risk management. Articles were selected from the Scopus and Web of Science databases based on predefined inclusion criteria and synthesized using thematic analysis. Relevant literature published between 2018 and 2025 was systematically analyzed to identify major themes and conceptual relationships. Findings: The review suggests that blockchain possesses several characteristics that may support transparency and fraud mitigation, including immutable records, distributed verification, smart contracts, and traceable audit trails. Existing empirical evidence from financial technology studies indicates that these mechanisms have the potential to strengthen digital trust and improve market accountability. However, their effectiveness remains dependent on institutional readiness, regulatory frameworks, and supporting digital infrastructure. Blockchain should be viewed not merely as a technological innovation but as a strategic mechanism that may contribute to improving transparency and reducing fraud risks in digital bullion trading. Conclusion: This study contributes by proposing an integrated conceptual framework that connects blockchain architecture, digital trust, market integrity, and anti-fraud mechanisms specifically within bullion markets. Future empirical studies are required to validate these conceptual relationships. Novelty/Originality of this article: The novelty of this study lies not in introducing blockchain technology itself, which has been extensively discussed in previous financial literature, but in developing an integrated conceptual perspective that specifically positions blockchain as a mechanism connecting transparency, digital trust, fraud prevention, and market integrity within digital bullion trading ecosystems.